Prevalence and determinants of under-nutrition among children aged 5-10 years in an urban area of Kancheepuram district, Tamil Nadu - M. K., Jasmine Sharmila; R., Umadevi Jeyakumar; V. M., Anantha Eashwar (International Journal Of Community Medicine And Public Health, 2020)
Background: Childhood is a phase of swift growth and development after infancy. One of the foremost public health problems in developing countries like India is extensive prevalence of under nutrition among school children resulting in delayed cognitive development and severe health impairment. Hence early detection helps in prompt prevention and treatment of complications. Aim was to assess the prevalence and factors associated with under-nutrition among children aged 5-10 years in an urban area of Kancheepuram district, Tamil Nadu. Methods: A descriptive cross sectional study conducted among 210 children in the age group of 5-10 years residing at Anakaputhur, an urban field practice area of Sree Balaji Medical College and hospital for a duration of 4 months by simple random sampling technique. A pre-tested semi-structured questionnaire was employed to interview the children and their mothers. The data obtained was subjected to statistical analysis using SPSS version 22. Results: Prevalence of underweight among children was found to be 52.4% of which 58.5% of the undernourished children were boys when compared to 47.4% among girls. Underweight was significantly associated with source of drinking water [(p<0.0125), OR=2.0566], episode of diarrhea [(p<0.0054), OR=2.3624] and ARI [(p<0.0000), OR= 8.6417] in the last 3 months, history of passing worms [(p<0.0348), OR=1.8878], meal frequency <3 times/day [(p<0.0000), OR=7.5432]. Conclusions: Half of the children (52.4%) in the study had poor nutritional status. To combat under-nutrition good living conditions, education to the mothers, clean water source, good personal hygiene, period deworming and delivery of integrated programs are recommended.